2023
DOI: 10.1038/s41598-023-46801-w
|View full text |Cite
|
Sign up to set email alerts
|

Startup process, safety and risk assessment of biomass gasification for off-grid rural electrification

Md Mashiur Rahman,
Ulrik Birk Henriksen,
Daniel Ciolkosz

Abstract: Biomass gasification has significantly advanced in terms of performance and is increasingly used in rural off-grid electricity applications. The downdraft gasifier is primarily used in biomass gasification applications, in which it functions as a reactor into which biomass and gasifying air are introduced to generate producer gas that is then used in an engine generator to produce electricity. However, the safety and stability of biomass gasification remain challenging and depend on several factors, such as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 15 publications
(24 reference statements)
0
0
0
Order By: Relevance
“…Alternative opportunities to use the biomass could be considered in further studies. The energy demand patterns imply that, in the DG model, the power plant is used for 11 h daily, whereas the OG model operates for 24 h. Biomass gasification system operation is complex not only because of the variety of processes involved and the high sensitivity of the system to operational parameters such as the biomass moisture and size, feeding rate, temperature reaction, and gas cleaning [60,61,64], but also because of the high risks of fire, explosion, and toxic emissions due to the high operating temperature, which must be mitigated by strict operational procedures [63]. Therefore, gasification systems require a large and well-trained team to avoid shutdowns or inefficient operations, and to guarantee their safety.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternative opportunities to use the biomass could be considered in further studies. The energy demand patterns imply that, in the DG model, the power plant is used for 11 h daily, whereas the OG model operates for 24 h. Biomass gasification system operation is complex not only because of the variety of processes involved and the high sensitivity of the system to operational parameters such as the biomass moisture and size, feeding rate, temperature reaction, and gas cleaning [60,61,64], but also because of the high risks of fire, explosion, and toxic emissions due to the high operating temperature, which must be mitigated by strict operational procedures [63]. Therefore, gasification systems require a large and well-trained team to avoid shutdowns or inefficient operations, and to guarantee their safety.…”
Section: Discussionmentioning
confidence: 99%
“…Ruiz et al [60] reported the formation of tars in syngas and the development of cost-effective solutions to clean it as one of the major challenges to the commercial deployment of gasification, as have other studies [9,42,61,62]. Rahman et al [63] raised the issue of the gasifier's operation safety, highlighting the risks of fire, explosion, toxic emissions, and the corrosion of the reactor, all related to the high operating temperatures and the nature of the gases produced. Safety systems must be installed, and strict operational procedures must be implemented, to reduce hazards.…”
Section: Barriers and Challenges To Small-scale Biomass Gasificationmentioning
confidence: 99%
“…In some cases, microalgae also served as a beneficial feedstock. Other than the feedstocks characteristics, numerous factors, including reactor type, feedstock size and process time of the feedstock and volatile matters, also impact the yield of the biofuel 11 . The most popular reactors for slow pyrolysis are drums, rotatory kilns and screw types.…”
Section: Introductionmentioning
confidence: 99%